EFL Student-Teachers' Voice in Using Self-Regulated Behavior Strategies in Extensive Listening Activities - Vera Nursyarah; Nur Arifah Drajati; Ngadiso Ngadiso (EDULANGUE, 2019)
Self-regulated learning skills are essential for students since self-regulated learners are more responsible for their own learning. Drawing on Zimmerman’s (2000) framework regarding self-regulation, this narrative study looked closely into self-regulatory behaviors of English student-teachers and the ways they regulated their Extensive Listening activities. The data were gathered from students’ learning journals and semi-structured interview. Two EFL student-teachers from an English department of an Indonesian University who were successfully managing their consistency in their Extensive Listening activities were selected as the participants. The findings showed that EFL student teachers used their self-regulatory behavior strategies in different cyclical phases (forethought, performance or volitional control, and self-reflection) in Extensive Listening activities. By experiencing and knowing what self-regulatory behavior strategies they use and how they are used, English student-teachers are expected to be able to transmit their knowledge of self-regulation in learning to their students in the future of ELT teaching.